Answer:
(x-5)(x-5)
Step-by-step explanation:
Ok... This ones actually pretty simple.
So all you have to do is find 2 numbers that add up to -10, and multiply to 25. You will quickly realize that the only 2 numbers that do that are -5 and -5. Then, all you have to do is write the now factored equation. (x-5)(x-5)
There are 2 ways to check your work. The first is to FOIL (first, inside, outside, last). This should get you back to your original equation
The second way to do it is to plug it into a graphing program. If you graph your factored equation and your original equation, they should be the same!
I hope this helps!
If you have any other questions just feel free to ask me.
For this case we must factor the following expression:
[tex]x ^ 2-10x + 25[/tex]
For this, we must find two numbers that when multiplied give 25 and when added to -10.
These numbers are -5 and -5:
[tex]-5-5 = -10\\-5 * -5 = 25[/tex]
Then, the factorization is given by:
[tex](x-5) (x-5)\\(x-5) ^ 2 [/tex]
Answer:
[tex](x-5) ^ 2 [/tex]
Vince bought 6 boxes of worms to use as
bait while fishing with his friends. If each
person uses exactly 3/8 of a box of worms,
how many people can share the worms?
A triangle is drawn on the coordinate plane. It is translated 4 units right and 3 units down. Which rule describes the translation?
Answer:
(x, y ) → (x + 4, y - 3 )
Step-by-step explanation:
A translation of 4 units to the right is a positive shift in the x- direction, that is,
The x- coordinate of the image is the original + 4
A translation of 3 units down is a negative shift in the y- direction, that is
The y- coordinate of the image is the original - 4
Putting the 2 together
(x, y ) → (x + 4, y - 3 )
your utility bill for april is $170. If you pay after the due date,a late payment panality of $7.72 is added? what is percent of penality?
Answer:
4.54%
Step-by-step explanation:
Step 1: Write the data
Total bill = $170
Penalty = $7.72
Percentage of penalty = ?
Step 2: Write the formula to find the percentage of penalty
Percentage of penalty = Penalty/Total bill * 100
Percentage of penalty = 7.72/170 * 100
Percentage of penalty = 4.54%
Therefore, the percent of penalty is 4.54%
!!
The equation tan(55°)= 15/b
can be used to find the length of AC
What is the length of Ac? Round to the nearest tenth.
Answer: [tex]AC=10.5[/tex]
Step-by-step explanation:
Assuming that [tex]b=AC[/tex] and given the following equation:
[tex]tan(55\°)=\frac{15}{b}[/tex]
You need to solve for "b" in order to find the lenght of AC asked in the exercise.
Therefore, with this procedure you get that the lenght of AC is the following:
[tex]\frac{15}{tan(55\°)}=b[/tex]
[tex]b=AC=10.5[/tex]
Which of the following is an example of a conditional probability?
O
A. The probability that a volcano will erupt tomorrow.
O
B. The probability that a person will not fall while skating.
O
C. The probability a person will ace a test given that the person got a
good night's sleep the previous night.
O
D. The probability that a road will be closed or a certain song will
come on the radio.
Answer:
The probability a person will ace a test given that the person got a
good night's sleep the previous night.
Step-by-step explanation:
A conditional probability is a probability that something will occur given that something else has happened.
C The probability a person will ace a test given that the person got a
good night's sleep the previous night.
The equation F=
C +32 gives the Fahrenheit temperature F corresponding to the Celsius temperature C
Find the Fahrenheit temperature equivalent to 30°C
The Fahrenheit temperature equivalent to 30°C is °F
(Simplify your answer. Type an integer or a decimal.)
Answer:62
Step-by-step explanation:
F=c+32
C=30
F=30+32
F=62
The Fahrenheit temperature equivalent to 30°C (using the formula F = C + 32) is 62°F.
The Fahrenheit temperature equivalent to 30°C can be found using the temperature conversion formula F = C + 32, where F is the temperature in Fahrenheit and C is the temperature in Celsius.
To find the temperature in Fahrenheit, substitute 30 for C:
F = 30°C + 32 = 62°F
When the factors of a trinomial are (x+p) and (x-q) then the coefficient of the x-term in the trinomial is:
Answer:
p - q
Step-by-step explanation:
Given the factors
(x + p)(x - q) ← expanding the factors
= x² - qx + px - pq ← collect like terms
= x² + px - qx - pq ← factor out x in each of the x- terms
= x² + (p - q)x - pq
The coefficient of the x- term is p - q
Jermiah makes a recipe that calls for 1 1/2 cups of flour and 3/4 stick of butter. If Jermiah uses 3 sticks of butter, how many cups of flour will he need
Answer:
The answer is 6 cups of flour.
To find the amount of flour needed for 3 sticks of butter, a proportion based on the original recipe ratio is used, resulting in 6 cups of flour.
Jermiah's recipe calls for 1 1/2 cups of flour for every 3/4 stick of butter. Therefore, if he uses 3 sticks of butter, we need to find out how many cups of flour that corresponds to.
To determine the amount of flour needed, we set up a proportion, where the original amount of butter and flour are proportional to the new amount of butter and flour.
Since 3/4 stick of butter corresponds to 1 1/2 cups of flour, 3 sticks of butter would be 4 times as much, because 3 divided by 3/4 equals 4. Therefore, he will need 4 times the original amount of flour.
Here is the math: 1 1/2 cups of flour x 4 = 6 cups of flour.
slope 1/2, passes through (6,4)
Write in slope-intercept form
Answer:
[tex]\large\boxed{y=\dfrac{1}{2}x+1}[/tex]
Step-by-step explanation:
[tex]\text{The slope-intercept form of an equation of a line:}\\\\y=mx+b\\\\m-slope\\b-y-intercept\\\\\text{We have:}\ m=\dfrac{1}{2}\ \text{and the point}\ (6,\ 4).\\\\\text{The equation:}\ y=\dfrac{1}{2}x+b.\\\\\text{Put the coordinates of the point to the equation:}\\\\4=\dfrac{1}{2}(6)+b\\\\4=3+b\qquad\text{subtract 3 from both sides}\\\\1=b\to b=1\\\\\text{Finally:}\\\\y=\dfrac{1}{2}x+1[/tex]
Write the equation of the line that passes
through the points (0,-5) and (1,-9).
I’m stuck....:(
Answer:
The slope is -4.
Step-by-step explanation:
Slope formula:
[tex]\displaystyle \frac{y_2-y_1}{x_2-x_1}=\frac{rise}{run}[/tex]
[tex]\displaystyle \frac{(-9)-(-5)}{1-0}=\frac{-4}{1}=-4[/tex]
Therefore, the slope is -4, and the correct answer is -4.
Hope this helps!
What are the slope and the y-intercept of the linear function that is represented by the equation y=-10x+1
The slope is [tex]-10[/tex] and the y-intercept is [tex]1[/tex].
Explanation:This function is written in slope-intercept form, which is [tex]y=mx+b[/tex]. In this form, [tex]m[/tex] is the slope and [tex]b[/tex] is the y-intercept.
In this case, [tex]m=-10[/tex] and [tex]b=1[/tex], so those are the answers to this problem.
For this case we have that by definition, the equation of a line of the slope-intersection form is given by:
[tex]y = mx + b[/tex]
Where:
m: It's the slope
b: It is the cutoff point with the y axis
We have the following equation:
[tex]y = -10x + 1[/tex]
So we have to:
[tex]m = -10\\b = 1[/tex]
Answer:
[tex]m = -10\\b = 1[/tex]
What is the following product 3 square root 2(5 square root 6-7 square root 3
Answer:
30√3 - 21 √6
Step-by-step explanation:
The given expression is:
3√2 (5√6 -7√3)
We cannot subtract the values inside the bracket because the values inside the radicals are not same.
So multiply 3√2 with the bracket.
=3*5√2*6 - 3*7√2*3
=15√12 - 21√6
Now break √12
=15√4*3 - 21√6
write √4*3 separately:
=15√4 *√3 - 21√6
We know that √4 = 2
=15*2*√3 - 21√6
=30√3 - 21 √6
Therefore the answer is 30√3 - 21 √6 ....
The graph below shows the solution for the following system.
{f(x)=2x−3
g(x)=2^x−4
Linear function passing through (0, negative 3), (1.5, 0) & about (2.7, 2.3).
Exponential function passing through (negative 3, negative 4), (0, negative 3), (2,0) & about (2.7, 2.3).
Which statements are true?
Select all that apply.
x=0 is a solution to the system.
(1.5,0) and (2,0) are solutions to the system because the graphs of f(x) and g(x) cross the x-axis at those points.
When x≈2.7, the graphs of f(x) and g(x) intersect because they are equal to each other at that value.
f(x)=g(x) when x=0.
Answer:
TRUE:
When x≈2.7, the graphs of f(x) and g(x) intersect
f(x)=g(x) when x=0
Step-by-step explanation:
The graphs of two function y=f(x) and y=g(x) are shown in attached diagram.
These two graphs intersect at two points (0,-3) and about (2.7,2.3). This means that
f(0)=g(0)=-3
and
f(2.7)=g(2.7)=2.3
So, x=0, y=-3 is the solution to the system (the solution to the system is ordered pair (x,y), not only x)
Points (1.5,0) and (2,0) are not solutions, because they are not points of graphs intersection.
When x≈2.7, the graphs of f(x) and g(x) intersect (TRUE)
f(x)=g(x) when x=0 (TRUE)
Answer:
f(x)=g(x) when x=0.
x=0 is a solution to the system.
When x≈2.7, the graphs of f(x) and g(x)intersect because they are equal to each other at that value.
What is the slope-intercept equation for the line below?
(4.1)
(0, -4)
Answer:
y=5/4x-4
Step-by-step explanation:
C. y = 5/4x - 4.
What is slope-intercept?One of the three ways we may express a straight line is in slope-intercept form. The other forms are known as point slope form and standard form, however in this section we will mostly use slope-intercept form. The slope-intercept form is used to write a line's equation as y = mx + c.
You may be aware that a point's coordinates on a graph are x and y.
Given two coordinates of a line from that, we can calculate the slope.
slope m = (y₂ - y₁) / (x₂- x₁)
m = 5/4
Put the value of m and one coordinate value in the slope-intercept equation
-4 = 5/4 * 0 + c
c = -4
therefore slope-intercept equation of given coordinates is y = 5/4x - 4.
Learn more about slope here:
https://brainly.com/question/3605446
#SPJ2
Marcus loves baseball and wants to create a home plate for his house. Marcus needs to calculate the area of the home plate at the ball field so he can reconstruct it when he gets home. Calculate the area of the polygon.
TYSM
Answer:
Area of the polygon = 59 in²
Explanation:
From the given diagram, we can note that the given polygon is composed of an upper triangle, a side triangle and a rectangle
Therefore:
Area of polygon =
area of upper triangle + area of side triangle + area of rectangle
1- getting the area of the upper triangle:
We have:
base of triangle = 7 in
height of triangle = 6 in
Therefore:
Area of upper triangle = [tex]\frac{1}{2}*base*height = \frac{1}{2}*7*6=21[/tex] in²
2- getting the area of the side triangle:
We have:
base of triangle = 4 in
height of triangle = 5 in
Therefore:
Area of upper triangle = [tex]\frac{1}{2}*base*height = \frac{1}{2}*4*5=10[/tex] in²
3- getting the area of the rectangle:
We have:
length of rectangle = 7 in
width of rectangle = 4 in
Therefore:
Area of rectangle = length x width = 7 x 4 = 28 in²
4- getting the total area of the polygon:
Area of polygon =
area of upper triangle + area of side triangle + area of rectangle
Therefore:
Area of polygon = 21 + 10 + 28 = 59 in²
Hope this helps :)
What’s the exact value of Cos(127.5)? Using trig identities like half angle and PLEASE EXPLAIN
To find the exact value of cos(127.5), we can use the half angle identity for cosine. By substituting the angle into the half angle identity and simplifying, we find that cos(127.5) is approximately ±0.99992.
Explanation:The cosine function is a trigonometric function that relates the angle of a right triangle to the ratio of the adjacent side to the hypotenuse. To find the exact value of cos(127.5), we can use the half angle identity for cosine. This identity states that cos(θ/2) = ±√((1 + cos(θ))/2), where θ is the original angle.
In this case, we have θ = 255 degrees (since 127.5 is half of 255). Using the half angle identity, we can calculate cos(127.5) as follows:
Convert 255 degrees to radians: 255° × π/180 = 4.45 radiansSubstitute θ = 4.45 into the half angle identity: cos(127.5) = ±√((1 + cos(4.45))/2)Calculate cos(4.45): cos(4.45) ≈ 0.9997Substitute the value into the half angle identity: cos(127.5) = ±√((1 + 0.9997)/2)Simplify the square root: cos(127.5) ≈ ±√(1.9997/2)Divide the numerator and denominator by 2: cos(127.5) ≈ ±√0.99985Take the square root: cos(127.5) ≈ ±0.99992Therefore, the exact value of cos(127.5) is approximately ±0.99992.
Learn more about Cosine function here:https://brainly.com/question/29277391
#SPJ3
Write the polar coordinates (3, 3) in rectangular form,
a. (0,3)
c. (-3,0)
b. (3,0)
d. (0,-3)
Please!!!!! I really need help on this one
Answer:
C
Step-by-step explanation:
(-3,0)
I did it in the quiz and the test.
Got it correct.
What is the x-interception of the Logarithmic function??
The answer is:
Why?To find the x-interception of the given function, we just need to isolate the variable "x", by making the function (y) equal to 0.
So, we are given the function:
[tex]F(x)=y=Log_{0.71}(x)[/tex]
Now, making y equal to 0, to isolate "x", we have:
[tex]y=Log_{0.71}(x)\\\\0=Log_{0.71}(x)[/tex]
[tex]0=Log_{0.71}(x)\\\\0.71^{0}=0.71^{Log_{0.71}(x)}} \\\\1=x[/tex]
We have that the x-intercept of the logarithmic function is located at (1,0)
Hence, the correct answer is:
B. (1,0).
Have a nice day!
Note: I have attached a picture for better understanding.
Jackrabbit are capable of reaching speeds up to 40 miles per hour. How fast is this in feet per second
Answer:
58.6667
Step-by-step explanation:
if you see there are 5280 ft in 1 mile so use ur brain
Answer:
58.67 feet per second.
Step-by-step explanation:
We have been given that Jackrabbit are capable of reaching speeds up to 40 miles per hour. We are asked to represent this speed in feet per second.
We know that 1 mile equals 5280 feet.
We also know that 1 hour equals 3600 seconds.
[tex]\text{Speed of jackrabbit}=\frac{\text{40 miles}}{\text{Hour}}\times \frac{\text{5280 feet}}{\text{Mile}}\times \frac{\text{1 hour}}{\text{3600 sec}}[/tex]
[tex]\text{Speed of jackrabbit}=\frac{40 \times\text{5280 feet}}{\text{3600 sec}}[/tex]
[tex]\text{Speed of jackrabbit}=\frac{211200\text{ feet}}{\text{3600 sec}}[/tex]
[tex]\text{Speed of jackrabbit}=\frac{58.67\text{ feet}}{\text{3600 sec}}[/tex]
Therefore, the speed of jackrabbit is 58.67 feet per second.
Find the area of the shaded region.
Round to the nearest tenth.
9.28 cm
68.90
Area = [?] cm?
I really need help pretty quick on this one. So plz hurry if u can.
Answer:
The area of the shaded region is [tex]11.6\ cm^{2}[/tex]
Step-by-step explanation:
we know that
The area of the shaded region is equal to the area of the sector of circle of angle 68.9 degrees minus the area of the isosceles triangle
step 1
Find the area of sector of the circle
The area of circle is equal to
[tex]A=\pi r^{2}[/tex]
assume
[tex]\pi =3.14[/tex]
[tex]r=9.28\ cm[/tex]
substitute
[tex]A=(3.14)(9.28)^{2}[/tex]
[tex]A=270.41\ cm^{2}[/tex]
Remember that the area of a circle subtends a central angle of 360 degrees
so
using proportion Find out the area of a sector with a central angle of 68.90 degrees
Let
x -----> the area of a sector
[tex]270.41/360=x/68.90\\\\x=68.90*270.41/360\\\\x=51.75\ cm^{2}[/tex]
step 2
Find the area of the isosceles triangle
Applying the law of sines
The area is equal to
[tex]A=(1/2)r^{2}sin(68.90)[/tex]
we have
[tex]r=9.28\ cm[/tex]
substitute
[tex]A=(1/2)(9.28)^{2}sin(68.90)=40.17\ cm^{2}[/tex]
step 3
Find the area of the shaded region
[tex]51.75-40.17=11.58\ cm^{2}[/tex]
Round to the nearest tenth
[tex]11.58=11.6\ cm^{2}[/tex]
The calculated area of the shaded region is 11.6 square cm
How to determine the area of the shaded region.from the question, we have the following parameters that can be used in our computation:
The circle
The area of the shaded region is calculated as
Area of shaded region = Area of sector - Area of triangle
Using the respective formulas, we have
Area of shaded region = 68.9/360 * 3.14 * 9.28 * 9.28 - 1/2 * 9.28 * 9.28 * sin(68.9)
Evaluate
Area of shaded region = 11.6
Hence, the area of the shaded region is 11.6 square cm
Read more about area at
https://brainly.com/question/33242443
#SPJ3
Find x Round to the nearest tenth
Answer:
15.5
Step-by-step explanation:
So the formula here is the square of the tangent length is equal to the product of the exterior part of the secant line and total length of the secant.
So that means we have x^2=10(14+10).
After simplifying the right hand side we have the equation is x^2=10(24) or x^2=240.
To get rid of the square on the x, we square root both sides.
x=sqrt(240)
x=15.49193338
To the nearest tenths, the answer is x=15.5
So 15.5 inches is the length of x.
The lengths of two sides of a right triangle are 12 inches and 15 inches. What is the difference between the two possible
lengths of the third side of the triangle? Round your answer to the nearest tenth.
10.2 inches
24.0 inches
28.2 inches
30.0 inches
Answer:
The correct option is A
Step-by-step explanation:
Lets suppose that the third side is hypotenuse.
We will apply Pythagorean theorem:
c²= a²+b²
where,
a=12 inches
b=15 inches
Now substitute the values in the theorem:
c²=(12)²+(15)²
c²=144+225
c²=369
Take square root on both sides:
√c²=√369
c= 19.2 inches.
Now assume that the third side is a leg:
Here we will find the value of b.
a=12 inches
c= 15 inches.
b= ?
Now substitute the values in the theorem:
c²=a²+b²
(15)²=(12)²+b²
225=144+b²
Move the constant to the L.H.S
225-144=b²
81=b²
Take square root on both sides:
√81=√b²
9=b
Now we will find the difference of the third sides:
19.2-9 = 10.2
Thus the length of the third side is 10.2 inches
The correct option is A....
Answer:
A.
Step-by-step explanation:
Figure A is a scale image of Figure B. What is the value of x?
In a scale model, Figure A has one side measuring 45 units and another side measuring x, while Figure B has corresponding sides of 27 and 18 units. By setting up a proportion, x is determined to be 30 units.
To find the value of x, we can set up a proportion based on the given information:
In Figure A, one side is 45, and in Figure B, it corresponds to a side of 27.
In Figure A, the other side is x, and in Figure B, it corresponds to a side of 18.
So, we can set up the following proportion:
(45 / 27) = (x / 18)
Now, cross-multiply and solve for x:
45 * 18 = 27x
810 = 27x
Now, divide by 27 to find the value of x:
x = 810 / 27
x = 30
So, the value of x is 30.
Learn more about scale model here:
https://brainly.com/question/29367001
#SPJ2
simplify 3y - 5(y + 2) completely
Answer:
A
Step-by-step explanation:
3y (-5)(y+2)
3y(-5y-10)
3y-5y-10
-2y-10
-2y-10
3y - 5(y +2)
Use the distributive property:
3y - 5y +10
Combine like terms:
-2y+10
The answer is B.
Help me with this please
Answer:
[tex]\large\boxed{(b)\ \dfrac{x+2}{x-3}}[/tex]
Step-by-step explanation:
[tex]\dfrac{1}{x+1}+\dfrac{x}{x-3}-\dfrac{-x-5}{x^2-2x-3}=(*)\\\\x^2-2x-3=x^2-3x+x-3=x(x-3)+1(x-3)=(x-3)(x+1)\\\\(*)=\dfrac{1(x-3)}{(x+1)(x-3)}+\dfrac{x(x+1)}{(x+1)(x-3)}+\dfrac{-(-x-5)}{(x+1)(x-3)}\\\\=\dfrac{x-3+x^2+x+x+5}{(x+1)(x-3)}=\dfrac{x^2+(x+x+x)+(-3+5)}{(x+1)(x-3)}\\\\=\dfrac{x^2+3x+2}{(x+1)(x-3)}=\dfrac{x^2+2x+x+2}{(x+1)(x-3)}=\dfrac{x(x+2)+1(x+2)}{(x+1)(x-3)}\\\\=\dfrac{(x+2)(x+1)}{(x+1)(x-3)}\qquad\text{cancel (x + 1)}\\\\=\dfrac{x+2}{x-3}[/tex]
Right triangle ABC and its image, triangle A'B'C' are shown in the image attached.
Algebraically prove that a clockwise and counterclockwise rotation of 180° about the origin for triangle ABC are equivalent rotations.
Answer:
See explanation
Step-by-step explanation:
Triangle ABC ha vertices at: A(-3,6), B(0,-4) and (2,6).
Let us apply 90 degrees clockwise about the origin twice to obtain 180 degrees clockwise rotation.
We apply the 90 degrees clockwise rotation rule.
[tex](x,y)\to (y,-x)[/tex]
[tex]\implies A(-3,6)\to (6,3)[/tex]
[tex]\implies B(0,4)\to (4,0)[/tex]
[tex]\implies C(2,6)\to (6,-2)[/tex]
We apply the 90 degrees clockwise rotation rule again on the resulting points:
[tex]\implies (6,3)\to A''(3,-6)[/tex]
[tex]\implies (4,0)\to B''(0,-4)[/tex]
[tex]\implies (6,-2)\to C''(-2,-6)[/tex]
Let us now apply 90 degrees counterclockwise rotation about the origin twice to obtain 180 degrees counterclockwise rotation.
We apply the 90 degrees counterclockwise rotation rule.
[tex](x,y)\to (-y,x)[/tex]
[tex]\implies A(-3,6)\to (-6,-3)[/tex]
[tex]\implies B(0,4)\to (-4,0)[/tex]
[tex]\implies C(2,6)\to (-6,2)[/tex]
We apply the 90 degrees counterclockwise rotation rule again on the resulting points:
[tex]\implies (-6,-3)\to A''(3,-6)[/tex]
[tex]\implies (-4,0)\to B''(0,-4)[/tex]
[tex]\implies (-6,2)\to C''(-2,-6)[/tex]
We can see that A''(3,-6), B''(0,-4) and C''(-2,-6) is the same for both the 180 degrees clockwise and counterclockwise rotations.
Triangle ABC ha vertices at: A(-3,6), B(0,-4) and (2,6).
Let us apply 90 degrees clockwise about the origin twice to obtain 180 degrees clockwise rotation.
We apply the 90 degrees clockwise rotation rule.
(x,y) --- (y, -x)
A(-3, 6) > (6, 3)
B(0, 4) > (4, 0)
C(2, 6) > (6, -2)
We apply the 90 degrees clockwise rotation rule again on the resulting points:
(6, 3) > A'(-3, 6)
(4, 0) > B'(0, -4)
(6, -2)> C'(-2, -6)
Let us now apply 90 degrees counterclockwise rotation about the origin twice to obtain 180 degrees counterclockwise rotation.
We apply the 90 degrees counterclockwise rotation rule.
(x,y) --- (-y, x)
A(-3, 6) > (-6, -3)
B(0, 4) > (-4, 0)
C(2, 6) > (-6, 2)
We apply the 90 degrees counterclockwise rotation rule again on the resulting points:
(-6, -3) > A'(3, -6)
(-4, 0) > B'(0, -4)
(-6, 2) > C'(-2, -6)
We can see that A'(3,-6), B'(0,-4) and C'(-2,-6) is the same for both the 180 degrees clockwise and counterclockwise rotations.
Ez why to copy
WILL GIVE BRAINLEIST NEED TO TURN IN BY 9 P.M. PLS HURRY SUPER EASY
A. What 3 consecutive even numbers added together equal 42? Use the equation n+(n+2) +(n+4)=42 to help you solve
B. Give an example of an equation that has a solution of 5.
Answer:
A) 12,14,16
B) 3x+1=16
Step-by-step explanation:
A)
They already gave you the equation to solve:
n+(n+2)+(n+4)=42
n+n+2+n+4=42
Put like terms together:
n+n+n+2+4=42
Combine the like terms:
3n+6=42
Subtract 6 on both sides:
3n=42-6
Simplify:
3n=36
Divide both sides by 3:
n=36/3
Simplify:
n=12
If n=12,
then
n+2=14 and
n+4=16.
Check the addition of those numbers: 12+14+16=26+16=42.
B)
There is a lot of equations that have a solution of 5.
It might be good start with x=5.
Then just remember whatever you do to one side, you must do to the other.
x=5
Multiply both sides by 3:
3x=15
Add 1 on both sides:
3x+1=16
An example of equation that solution 5 is 3x+1=16.
Which expressions have a value of - 1/64 ? Check all that apply.
Answer:
That may be one of the answers but it is check all that apply
Step-by-step explanation:
Let f(x)=x + 1 and g(x)=x2-x. Find and simplify the expression.
(f+g)(2)
Final answer:
To simplify (f+g)(2) with given functions f(x)=x+1 and g(x)=x^2-x, calculate the functions' values at x=2 and sum them, resulting in (f+g)(2) = 5.
Explanation:
To find and simplify the expression (f+g)(2), you first need to determine the individual functions f(x) and g(x) at the value x = 2, and then sum them.
The function f(x) is given by f(x) = x + 1. At x = 2, f(2) = 2 + 1 = 3.
The function g(x) is given by g(x) = x2 - x. At x = 2, g(2) = 22 - 2 = 4 - 2 = 2.
Adding these two results together, we get (f+g)(2) = f(2) + g(2) = 3 + 2 = 5.
what is the sum of the geometric sequence-1,6,36 if there are 6 terms
Answer:
The sum is [tex]9,331[/tex]
Step-by-step explanation:
we have
[tex]1,6,36,...[/tex]
we have
[tex]a1=1[/tex]
[tex]a2=6[/tex]
[tex]a3=36[/tex]
Find the common ratio r
[tex]a2/a1=6/1=6[/tex]
[tex]a3/a2=36/6=6[/tex]
The common ratio is r=6
The formula to calculate the sum in a geometric sequence is equal to
[tex]S=a1\frac{(1-r^{n})}{(1-r)}[/tex]
where
n is the number of terms
r is the common ratio
a1 is the first term
we have
[tex]n=6[/tex]
[tex]a1=1[/tex]
[tex]r=6[/tex]
substitute
[tex]S=(1)\frac{(1-(6)^{6})}{(1-6)}[/tex]
[tex]S=\frac{(1-(6)^{6})}{(-5)}[/tex]
[tex]S=9,331[/tex]